Kejahatan Terorganisir Transnasional: Penyelundupan Manusia Dalam Jaringan Snakeheads Cina - Arindrayani, Angelica Putri; Anabarja, Sarah (Intermestic: Journal of International Studies, 2024)
Human smuggling as an embodiment of transnational organized crime is a form of transnational illegal trade. A widely traded commodity is migrants, and one human smuggling network with an extensive cross-border network is China-based Snakeheads. This article applies qualitative methods with secondary data collection to elaborate on the development and interaction patterns of Chinese Snakeheads as well as their resilience strategies. By utilizing the social network theory and dependency theory, the results show that both smugglers and migrants have a strong urge to leave no trace by using the social ties and resources they have. Smuggling routes often involve transit countries, where such countries may have incentives to allow efficient underground smuggling systems rather than risk-generating longer smuggling routes. The smugglers themselves have developed various strategies to encourage their transactions, flexibility, and resilience as a smuggling business to ensure the success of the smuggling process.